Electrochemical Oxidation of Small Organic Molecules on Au Nanoparticles with Preferential Surface Orientation. Issue 7 (15th April 2015) - Monzó, Javier; Malewski, Yvonne; Vidal‐Iglesias, Francisco J.; Solla‐Gullon, Jose; Rodriguez, Paramaconi
Abstract The surface orientation effect on the oxidation of small organic molecules such as methanol, formaldehyde, ethanol, and glycerol has been studied on Au nanoparticles in alkaline medium. Two sets of Au nanoparticles enriched in (100) and (111) facets were synthetized by using colloidal methods in presence of cetyltrimethylammonium bromide. The nanoparticles were physically characterized by using TEM and XRD and electrochemically characterized by using Pb underpotential deposition as a surface‐structure probe. It is reported that, although methanol oxidation was similar in both types of nanoparticles, the oxidation of formaldehyde presented a clear surface orientation effect. For this reaction, nanoparticles with (111) preferential orientation presented higher current densities at low potentials, whereas Au(100) nanoparticles exhibited higher activity at potentials more positive than 1.0 V versus RHE. On the other hand, for glycerol and ethanol oxidations, the onset of the reaction was similar in both types of particles, although Au(111) nanoparticles showed higher current densities than the Au(100) ones.